PENERAPAN NILAI-NILAI HADIS SHAHIH BUKHARI NO. 6159 DALAM MENANGGAPI JUDI ONLINE BAGI GENERASI MUDA - Mukhammad Alfani; Farichatul Fauziyah; Ahmad Zamzami Mudhofar Abu Zayyid (DIRAYAH : Jurnal Ilmu Hadis, 2024)
This article discusses the application of values from Sahih Bukhari Hadith No. 6159 in responding to online gambling among the younger generation. Online gambling is a serious challenge that can damage the morals, mental health and financial stability of youth. This study aims to identify how hadith values can be applied as a moral guide in dealing with online gambling, as well as the role of family and community in educating young people about the dangers of gambling. The method used was a qualitative approach, which allowed for an in-depth understanding of the impact of gambling and its prevention strategies. The results showed that online gambling has a negative impact on adolescents, including decreased academic performance, damage to social relationships, and financial problems. The accessibility of technology and peer influence are the main driving factors. The study concluded that effective prevention measures include education about the dangers of gambling, religious guidance, family support, and a crackdown on gambling promotion. Islamic values-based approaches, including moral education and community strengthening, are expected to help adolescents avoid harmful online gambling practices. This conclusion emphasizes the importance of comprehensive efforts to protect young people from the negative impacts of online gambling.